Belo Monte: Actors and arguments in the struggle over Brazil's most controversial Amazonian dam - Fearnside, Philip Martin (Erde, 2017)
The reservoir of Brazil's Belo Monte Dam was filled in December 2015. The dam's planning, licensing and construction had rolled inexorably forward despite opposition from local victims of this development and from a wide array of other actors. Logical, legal and ethical arguments had less effect than the political and business forces prioritizing the dam. Part of the environmental destruction and human-rights violation at Belo Monte was apparently financed by taxpayers in North America and Europe with funds passed through Brazil's National Bank for Economic and Social Development (BNDES) from development policy loans (DPLs) to Brazil by the World Bank. This opens the opportunity for World Bank reforms to eliminate loopholes allowing funding through financial intermediaries. The human and environmental cost of Belo Monte should also give pause to governments and financial institutions in promoting dams as their primary response to energy issues.
Keywords: Dam Construction; Development Strategy; Environmental Impact; Financial Provision; Hydroelectric Power; Indigenous Population; Reservoir; Social Movement; World Bank; Amazonia; Belo Monte Dam; Europe; North America; Para [brazil]